Taḥbīb theory as neoplatonic emanationism? al-Jīlānī’s thought from riwāyah, dirāyah and riʿāyah perspectives - Jamil, Khairil Husaini; Kozhithodi, Salahudheen (2019)
ʿAbd al-Qādir al-Jīlāni, a 12th CE ḥanbalī mystic, argues repeatedly in his works, Futūḥ al-Ghayb and al-Fatḥ al-Rabbānī which are known for allegorical interpretation of prophetic ḥadīths, that a sufi may enjoy certain worldly pleasures after struggling through various stages of asceticism (zuhd). Ultimately, God will make him long for some worldly comforts according to His will – an act known as taḥbīb. al-Jīlānī substantiates this tahbīb theory with the famous ḥadīth which reads: “Two things of your world that were made lovely to me; the perfume and the women, and I found the coolness of my eyes in the prayer.” Unlike other exegetes of ḥadīth, al-Jīlānī focuses on the first word of the ḥadīth, ḥubbiba, which indicates that a person is made to love a certain subject. This somehow relates to emanation of love that comes for the Absolute or the Godhead. A similar notion of taḥbīb could be learned in later sufi works, though with different labels, such as al-Suhrawardī’s concept or ‘intihā’, which legitimises the apparently luxurious life style at a higher station of mysticism. The notion has also been observed in the Akbarian scheme of mysticism, attributed to al-Shaykh al-Akbar Ibn al-ʿArabī. Some have argued that elements from this sufistic notions are influenced by the neoplatonic emanationism. This may be concocted through the application of argumentum ex silentio in analysing al-Jīlānī’s deliberation. However, a counter argument could also be traditionally learned from the ḥadīth interpretive tradition. This article attempts to explore these issues within the context of al-Jīlānī’s works and to briefly highlight the possible connections between several areas of knowledge and philosophical endeavours within the relevant literatures.